Understanding the Impact of Competitive Advantage and Core Competency on Regional Tourism Revitalization: Empirical Evidence in Taiwan - Lee, Chaohsien; Wu, Chihkang; Jong, Din (Frontiers in Psychology, 2022)
ompetitive advantage and core competency are the unique capabilities and assets of an organization to provide valuable products or services to customers, thus giving the organization a better competitive position in the market than its competitors. In addition, how to create a competitive advantage is also one of the main objectives of business strategy. Therefore, this study focuses on understanding the decisive factors in regional revitalization and the relationship between business strategy, strategic alliance, and alliance performance through SMEs in Taiwan. This study selected a sample of 220 SMEs in Taiwan that had participated in the SME regional revitalization counseling program. The results showed that competitive advantage, core competency and strategic alliance partner selection had significant effects on alliance performance. In addition, core competency had an indirect effect on alliance performance through strategic alliance partner selection. However, competitive advantage did not have a significant effect on strategic alliance partner selection. Finally, this study proposes management implications and practical suggestions for SMEs' competitive advantage, core competency, and alliance performance.